Three Dimensional Finite Element Analysis of the Influence of Wood and Steel Mixed Static Pressure Single Pile Penetration on Adjacent Underground Pipeline - Liujie Du (Forest Chemicals Review)
The static pressure single pile of light wood structure shows good seismic performance in previous earthquakes. In this paper, the theoretical calculation method of four side clamped plate is simplified. In this paper, the circular hole expansion theory is used to analyze the soil squeezing effect of pile in the process of pile sinking. The test data show that the dead weight of jacked pile machine, static earth pressure and pile tip squeezing effect are the main forces of underground pipeline engineering. Based on this, this paper analyzes the mechanical model, finds the dangerous section and monitors it. In this paper, the ANSYS finite element simulation analysis of soil and supporting structure is carried out to verify the consistency between the displacement distribution and stress distribution of the underground structure and the actual engineering monitoring results.